Negative photoconductivity of InAs nanowires. Issue 2 (3rd December 2015) - Han, Yuxiang; Zheng, Xiao; Fu, Mengqi; Pan, Dong; Li, Xing; Guo, Yao; Zhao, Jianhua; Chen, Qing
Abstract : Negative photoconductivity is observed in InAs nanowires without a surface defective layer, and is induced by gas adsorption and the photogating effect. Abstract : Negative photoconductivity is observed in InAs nanowires (NWs) without a surface defective layer. The negative photoconductivity is strongly dependent on the wavelength and intensity of the light, and is also sensitive to the environmental atmosphere. Two kinds of mechanisms are discerned to work together. One is related to gas adsorption, which is photodesorption of water molecules and photo-assisted chemisorption of O2 molecules. The other one can be attributed to the photogating effect introduced by the native oxide layer outside the NWs.